A SURVEY OF PARTIAL EDENTULISM BASED ON KENNEDY'S CLASSIFICATION IN MAXILLARY ARCHES - Bharat Kumar; Asma Naz; Haroon Rashid (ziauddin University, 2018)
Objective: The objective of this study was to determine the various patterns of partial edentulism of maxillary arch in patients seen at department of Prosthodontics, Dr Ishrat- Ul -Ebad Khan Institute of Oral Health Sciences Karachi. Methods: The duration of the study was six months. Utilizing consecutive sampling technique, 527 patients were included. Partial edentulism pattern was recorded by visual examination using Kennedy's classification after applying Applegate's rules. Results: Class III dental arch was the most dominant pattern with class IV being the least in number. Kennedy's Class III modification 1 was the most common modification encountered and location of modification was mostly involved posterior areas. With increasing age, there was a decrease in percentage of Kennedy's class III and an increase in percentage of class I, class II and class IV patients. In present study gender had no significant effect on distribution of various Kennedy's classification, whereas there was statistically significant association between age and pattern of partial edentulism. Conclusion: The Kennedy's class III was the most common pattern of partial edentulism irrespective of age and gender Key words: Partial edentulism, Kennedy's classification, Modification, Maxillary arch